A Novel Bacterial ATP-Binding Cassette Transporter System That Allows Uptake of Macromolecules - Momma, Keiko (American Society for Microbiology, 2000)
A gram-negative bacterium, Sphingomonas sp. strain A1, isolated as a producer of alginate lyase, has a characteristic cell envelope structure and forms a mouth-like pit on its surface. The pit is produced only when the cells have to incorporate and assimilate alginate. An alginate uptake-deficient mutant was derived from cells of strain A1. One open reading frame, algS (1,089 bp), exhibiting homology to the bacterial ATP-binding domain of an ABC transporter, was cloned as a fragment complementing the mutation. algS was followed by two open reading frames, algM1 (972 bp) and algM2 (879 bp), which exhibit homology with the transmembrane permeases of ABC transporters. Disruption of algS of strain A1 resulted in the failure to incorporate alginate and to form a pit. Hexahistidine-tagged AlgS protein (AlgS(His6)) overexpressed in Escherichia coli and purified by Ni(2+) affinity column chromatography showed ATPase activity. Based on these results, we propose the occurrence of a novel pit-dependent ABC transporter system that allows the uptake of macromolecules.